1984
DOI: 10.1139/v84-035
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH and complexation on redox reactions between RS• radicals and flavins

Abstract: . On considkre brikvement les effets des changements observes dans les propriCtCs redox des radicaux sulfurts sur la complexation avec RS-et sur la protonation.[Traduit par le journal]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Given that theoretical considerations have indicated that the thiyl radical redox couple RS-/RS-has a one-electron potential of approx. 1.0 V, this provides further support for an electron-transfer mechanism (Ahmad & Armstrong, 1984).…”
Section: Gs + Nadh --Gs-+ Nadh + (25)supporting
confidence: 63%
“…Given that theoretical considerations have indicated that the thiyl radical redox couple RS-/RS-has a one-electron potential of approx. 1.0 V, this provides further support for an electron-transfer mechanism (Ahmad & Armstrong, 1984).…”
Section: Gs + Nadh --Gs-+ Nadh + (25)supporting
confidence: 63%
“…However, we observed no evidence for Of formation in the quenching of 10 2 by the cellular reducing agents, cysteine and glutathione. On thermodynamic grounds this is again reasonable because Ahmad and Armstrong [49] have estimated that E ° (RS'/RS-~)= +1.1 V, while for ~O 2 the one-electron reduction potential has been estimated to be E ° (102/Of) = +0.65 V [48]. Thus, the one-electron reduction of 10 2 by cysteine is highly unlikely.…”
mentioning
confidence: 77%
“…However, it is evident that this species would have to be an intermediate in the twoelectron reduction of F1 by RSSR-in the presence of RSH at pH 9 or 10, and the only significant product of that reaction was FlH- (14). Therefore it is evident that RSHF1.-is a fairly labile species, possible reacting with RS -as follows.…”
Section: Fad At P Hmentioning
confidence: 97%